الترابط النصي في رواية ضمير المتكلم لفيــصل الأحمر - منال عتارسية (My University, 2023)
Abstract : Textual linguistics is concerned with the study of spoken and written texts, with a focus on formal and moral tools that achieve textual coherence. This study has dealt with the appearances of consistency and harmony in the novel "pronoun" by Faisal Al-Ahmar, and this study has been divided into an introduction and two chapters, theoretical and applied, where the first chapter dealt with "the concept of : the text, discourse, and the difference between them, and the most important terms synonymous with textual linguistics, and the seven textual standards. The second chapter dealt with the study of consistency and harmony in the novel, and a conclusion that included the most important results --------------------------- ملخص : يهتم علم اللغة النصي بدراسة النصوص المنطوقة و المكتوبة مع التركيز على الأدوات الشكلية و المعنوية التي تحقق الترابط النصي. - و قد عالجت هذه الدراسة مظاهر الاتساق و الانسجام في رواية"ضمير المتكلم" لفيصل الأحمر، و قسمت الدراسة إلى مقدمة و فصلين، نظري و تطبيقي، حيث عالج الفصل الأول :مفهوم النص، و الخطاب، و الفرق بينهما، و أهم المصطلحات المرادفة لعلم اللغة النصي و المعايير النصية السبع، أما الفصل الثاني عالج دراسة الاتساق و الانسجام في الرواية، و خاتمة تضمنت أهم النتائج المتوصل إليها ------------------------------------- Résumé La linguistique textuelle s’intéresse à l’étude des textes parlés et écrits, en mettant l’accent sur les outils formels et moraux qui atteignent la cohérence textuelle. Cette étude a traité des manifestations de cohérence et d’harmonie dans le roman « pronom du locuteur » de Faisal Al-Ahmar, et a divisé l’étude en une introduction et deux chapitres, théorique et appliqué, où le premier chapitre traitait du concept de texte, du concept de discours et de la différence entre eux, et des termes les plus importants synonymes de linguistique textuelle et des sept normes textuelles.